Separation, hydrolysis and fermentation of pyrolytic sugars to produceethanol and lipids - Lian, J.; Chen, S.; Zhou, S.; Wang, Z.; O'Fallon, J.; Li, Chun-Zhu; Garcia-Perez, M. (Elsevier BV, 2010)
This paper describes a new scheme to convert anhydrosugars found in pyrolysis oils into ethanol and lipids. Pyrolytic sugars were separated from phenols by solvent extraction and were hydrolyzed into glucose using sulfuric acid as a catalyst. Toxicological studies showed that phenols and acids were the main species inhibiting growth of the yeast Saccharomyces cerevisiae. The sulfuric acids, and carboxylic acids from the bio-oils, were neutralized with Ba(OH)2. The phase rich in sugar was further detoxified with activated carbon. The resulting aqueous phase rich in glucose was fermented with three different yeasts: S. cerevisiae to produce ethanol, and Cryptococcus curvatus and Rhodotorula glutinis to produce lipids. Yields as high as 0.473g ethanol/g glucose and 0.167g lipids/g sugar (0.266g ethanol equivalent/g sugar), were obtained. These results confirm that pyrolytic sugar fermentation to produce ethanol is more efficient than for lipid production.